2020
DOI: 10.2196/preprints.19139
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 Mobile Positioning Data Contact Tracing and Patient Privacy Regulations: Exploratory Search of Global Response Strategies and the Use of Digital Tools in Nigeria (Preprint)

Abstract: BACKGROUND The coronavirus disease (COVID-19) pandemic is the biggest global economic and health challenge of the century. Its effect and impact are still evolving, with deaths estimated to reach 40 million if unchecked. One effective and complementary strategy to slow the spread and reduce the impact is to trace the primary and secondary contacts of confirmed COVID-19 cases using contact tracing technology. OBJECTIVE… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Some researchers have noted the usefulness of this data to public health and of data sharing across geographic borders [79]. Others have raised the need to assess the potential public health benefits of digital tools and health IT against the imperative to protect and maintain the privacy of patient health data [80][81][82][83][84][85].…”
Section: Governance and Use Of Data And Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers have noted the usefulness of this data to public health and of data sharing across geographic borders [79]. Others have raised the need to assess the potential public health benefits of digital tools and health IT against the imperative to protect and maintain the privacy of patient health data [80][81][82][83][84][85].…”
Section: Governance and Use Of Data And Informationmentioning
confidence: 99%
“…And the US CDC confirmed that all aspects of COVID-19 case investigation and contact tracing must be voluntary, confidential, and culturally appropriate [86]. Public health responses need to ensure that key elements of privacy are not abused or disregarded during emergencies [77,81].…”
Section: Governance and Use Of Data And Informationmentioning
confidence: 99%